Mycobacterium bovis in Swine: Spoligotyping of Isolates from Argentina - Soledad Barandiaran; Marcela Martínez Vivot; Eduardo Vicente Moras; Angel Adrián Cataldi; Martín José Zumárraga (Veterinary Medicine International)
A total of 143 Mycobacterium bovis isolates of pigs, from the most productive swine area in Argentina, were typed by spoligotyping. Twenty-two different spoligotypes were identified, and 133 (93%) isolates were grouped into 12 clusters. One of them, designed SB0140, was the most frequent because it held 83 (58%) isolates. This spoligotype also grouped 362 (43%) out of 841 isolates from previously typed cattle and, thus, constitutes the most frequent in our country. In addition, 135 (94%) isolates revealed spoligotypes identical to those of cattle, showing an epidemiological link. On the other hand, there were seven novel spoligotypes, six of which were also unique since they had only one isolate each. This study aimed to identify the spoligotypes of M. bovis isolated from pigs to contribute to a better understanding of the distribution of bovine tuberculosis in the main productive area of Argentina.